THE BIRTH OF THE MODERN SOVEREIGN STATE AND THE “DEPERSONALIZATION” OF INTERNATIONAL LAW (LATE 16TH – EARLY 19TH CENTURY) - Havrylenko, Oleksandr; Lohvynenko, Ihor; Lohvynenko, Yevheniia (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
In the article the historical and legal analysis of the process of establishing a modern sovereign state and its consequences for the architecture of international law in the period of late 16th – early 19th centuries has been conducted. It is shown that the establishment of sovereignty as the basic principle of political organization led to a radical transformation of the international legal order – from medieval universalism with a multi-layered structure of power and a multiplicity of subjects to a statecentered system in which the state itself is the sole and exclusive bearer of international legal personality.It has been proven that the process of “depersonalization” of international law, i.e., the displacement of the individual from the circle of direct subjects of legal relations, was a natural result of the formation of modern statehood. In the medieval order, certain categories of persons (merchants, diplomats, privileged corporations) could participate in international relations. However, with the transition to sovereignty, conceptually formulated in the works of Jean Bodin and Hugo Grotius, and later enshrined in the doctrine of Pufendorf, Bynkershoek, and Vattel, international law acquired a distinctly institutional, inter-state character. The Peace of Westphalia in 1648 symbolized this transformation by adopting the principles of territorial integrity, equality, and non-interference as the basis for international relations. These basic principles defined (these dominant principles defined) the state as a single, fully-fledged legal entity in the international arena. A historical and legal analysis of the process of establishing a modern sovereign state and its consequences for the architecture of international law in the early modern period (late 16th – early 19th centuries) has been conducted. It is shown that the establishment of sovereignty as the basic principle of political organization led to a radical transformation of the international legal order – from medieval universalism with a multi-layered structure of power and a multiplicity of subjects to a state-centered system in which the state itself is the sole and exclusive bearer of international legal personality.It has been proven that the process of “depersonalization” of international law, i.e., the displacement of the individual from the circle of direct subjects of legal relations, was a natural result of the formation of modern statehood. In the medieval order, certain categories of persons (merchants, diplomats, privileged corporations) could participate in international relations. However, with the transition to sovereignty, conceptually formulated in the works of Jean Bodin and Hugo Grotius, and later enshrined in the doctrine of Pufendorf, Bynkershoek, and Vattel, international law acquired a distinctly institutional, interstate character. The Peace of Westphalia in 1648 symbolized this transformation by adopting the principles of territorial integrity, equality, and non-interference as the basis for international relations. These basic principles defined (these dominant principles defined) the state as a single, fully-fledged legal entity in the international arena. A historical and legal analysis of the process of establishing a modern sovereign state and its consequences for the architecture of international law in the early modern period (late 16th – early 19th centuries) has been conducted. It is shown that the establishment of sovereignty as the basic principle of political organization led to a radical transformation of the international legal order – from medieval universalism with a multi-layered structure of power and a multiplicity of subjects to a state-centered system in which the state itself is the sole and exclusive bearer of international legal personality.It has been proven that the process of “depersonalization” of international law, i.e., the displacement of the indi-vidual from the circle of direct subjects of legal relations, was a natural result of the formation of modern statehood. In the medieval order, certain categories of persons (merchants, diplomats, privileged corporations) could participate in international relations. However, with the transition to sovereignty, conceptually formulated in the works of Jean Bodin and Hugo Grotius, and later enshrined in the doctrine of Pufendorf, Bynkershoek, and Vattel, international law acquired a distinctly institutional, inter-state character. The Peace of Westphalia in 1648 symbolized this transformation by adopting the principles of territorial integrity, equality, and non-interference as the basis for international relations. These basic principles defined (these dominant principles defined) the state as a single, fully-fledged legal entity in the international arena.Special attention is paid to the intellectual and conceptual aspects of the process of depersonalization: the transition from dynastic-personal logic of foreign relations to rationalized interaction between states; the formation of institutional diplomatic and military mechanisms; the consolidation of the doctrine of war as the prerogative of sovereigns. These changes were accompanied not only by a narrowing of the legal visibility of the individual, but also by the establishment of a positivist approach to international law as a system that regulates exclusively inter-state relations.e relationship between sovereignty and human rights, international responsibility of states, and legal personality of the individual. It is emphasized (the conviction is expressed) that studying the history of the depersonalization of international law allows for a better understanding of the origins of the modern global legal order and the contradic.Appropriate generalizations and conclusions have been made, in particular noting that the historical displacement of the individual from the international legal order had long-term consequences for the structure of international law in the 19th and 20th centuries, but at the same time laid the foundation for contemporary discussions about thtions that still determine the balance between the state and the individual in the international legal system.